Fumigant toxicity of Cymbopogon flexuosus lemon grass (Poaceae) essential oil to Sitophilus zeamais maize weevil (Coleoptera: Curculionidae) and phytotoxicity to Zea mays (Poaceae) - Mota Filho, Tarcísio Marcos Macedo [UNESP] (2023)
Compounds with insecticidal properties from plant essential oils are an alternative to manage Sitophilus zeamais. However, these compounds can affect physiological processes such as seed germination and plant growth. The objective was to evaluate the toxicity of the Cymbopogon flexuosus essential oil by fumigation to S. zeamais and its phytotoxic to Zea mays. The mortality of S. zeamais was 100% with the doses of 20, 30, 40 and 50 µL of the C. flexuosus essential oil per 20 g of grains. The lethal dose (LD50) of this essential oil was 9.3 µL and its lethal time (LT50) greater with the 10 µL (18.8 h) and lowest with that of 50 µL (0.02 h), respectively. The doses of 10 and 20 µL of the C. flexuosus essential oil did not reduce the seed germination and growth of corn plants. The essential oil of C. flexuosus is an alternative for the control of S. zeamais.